Gastrocnemius Medialis Architectural Properties in Flexibility Trained and Not Trained Child Female Athletes: A Pilot Study - Ioli Panidi; Gregory C. Bogdanis; Vasiliki Gaspari; Polyxeni Spiliopoulou; Anastasia Donti; Gerasimos Terzis; Olyvia Donti (MDPI AG, 2020)
Gastrocnemius medialis (GM) architecture and ankle angle were compared between flexibility trained (n = 10) and not trained (n = 6) female athletes, aged 8−10 years. Ankle angle, fascicle length, pennation angle and muscle thickness were measured at the mid-belly and the distal part of GM, at rest and at the end of one min of static stretching. Flexibility trained (FT) and not trained athletes (FNT) had similar fascicle length at the medial (4.19 ± 0.37 vs. 4.24 ± 0.54 cm, respectively, p = 0.841) and the distal part of GM (4.25 ± 0.35 vs. 4.18 ± 0.65 cm, respectively, p = 0.780), similar pennation angles, and muscle thickness (p > 0.216), and larger ankle angle at rest (120.9 ± 4.2 vs. 110.9 ± 5.8°, respectively, p = 0.001). During stretching, FT displayed greater fascicle elongation compared to FNT at the medial (+1.67 ± 0.37 vs. +1.28 ± 0.22 cm, respectively, p = 0.048) and the distal part (+1.84 ± 0.67 vs. +0.97 ± 0.97 cm, respectively, p = 0.013), larger change in joint angle and muscle tendon junction displacement (MTJ) (p < 0.001). Muscle thickness was similar in both groups (p > 0.053). Ankle dorsiflexion angle significantly correlated with fascicle elongation at the distal part of GM (r = −0.638, p < 0.01) and MTJ displacement (r = −0.610, p < 0.05). Collectively, FT had greater fascicle elongation at the medial and distal part of GM and greater MTJ displacement during stretching than FNT of similar age.